Aerodynamic surface pressure measurement in atmosphere and wind tunnel on a vertical axis wind turbine blade using pressure transducers - Oram, C. E. (Cranfield University, 1989)
Blade aerodynamic loads during operation of a wind turbine are poorly understood. Better measurements of these forces are needed for the design of more cost effective turbines. Existing estimates have been inferred from strain gauges in the blade structure, but such measurements are confused by the complexity of the blade's structural response. This present work has pressure tapped the blade surface and recorded at high speed, giving a highly detailed picture of dynamic events and blade loads. A modular blade was constructed for the 6m diameter Rutherford Appleton Vertical Axis Wind Turbine and instrumented with 32 semiconductor pressure transducers. A flow probe using a further three transducers projected ahead of the blade during some of the tests. The instrumented module was also operated in the oscillating mounting of the University of Glasgow's 1.6m by 2.4m wind tunnel. 1760 revolutions of data were collected in atmosphere with blade speed ratios down to about 2.0 and with a variety of blade leanout angles. Some 118 runs of a variety of waveform types and Reynolds numbers from 0.3 to 1.1 million, were collected from the blade in tunnel. Analysis of transducer calibrations concluded that the novel temperature correction technique used allowed pressure readings to 40Pa or better with 95% confidence. Confidence in measured pressures has allowed use of leading edge stagnation point pressure and position as a measure of wind in the rotor flowfield and as a surrogate measure of blade angle of attack. Blade surface pressures and integrated forces show the progression of dynamic stall with increase in wind speed, the dominance of the upstream blade pass in usefulness at low and moderate windspeeds and the rough equality at high windspeeds. Comparisons of wind tunnel and on-rotor data show much lower force and moment coefficients in atmosphere. Rotor 'goodness1 ratios of average blade tangential force to maximum blade and rotor force coefficients peak at a blade speed ratio of about 2.8. Goodness ratios show a mixed pattern with blade leanout. Analysis of pressure coefficient traces through stall indicate a mixed stall type starting at mid chord, moving to leading edge and thence to trailing edge.